2019
DOI: 10.1093/molbev/msz151
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis, Selection, and Novelty: Freshwater Adaptation in the Unique Sponges of Lake Baikal

Abstract: Freshwater sponges (Spongillida) are a unique lineage of demosponges that secondarily colonized lakes and rivers and are now found ubiquitously in these ecosystems. They developed specific adaptations to freshwater systems, including the ability to survive extreme thermal ranges, long-lasting dessication, anoxia, and resistance to a variety of pollutants. Although spongillids have colonized all freshwater systems, the family Lubomirskiidae is endemic to Lake Baikal and plays a range of key roles in this ecosys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 92 publications
0
25
0
Order By: Relevance
“…Our results showed that the genome size of Lubomirskia baikalensis (as determined using GenomeScope) is between 558 and 565 million base pairs (Kenny et al, 2019). This is larger than almost all known marine sponge genomes.…”
mentioning
confidence: 69%
“…Our results showed that the genome size of Lubomirskia baikalensis (as determined using GenomeScope) is between 558 and 565 million base pairs (Kenny et al, 2019). This is larger than almost all known marine sponge genomes.…”
mentioning
confidence: 69%
“…Several features of freshwater sponge biology make them excellent systems for studying the molecular and cellular pathways required for successful symbiosis yet freshwater sponge symbioses are poorly represented in the modern algal-based symbiosis literature. The emergence of molecular tools offers renewed opportunities to study sponge-based symbiotic systems, and freshwater sponges offer many tractable qualities of a model system to study intracellular symbioses (Kenny et al, 2019;Kenny et al, 2020).…”
Section: Both Of the Classic Examples Of Endosymbiosis Mentioned Prevmentioning
confidence: 99%
“…Thus, freshwater sponges have the potential to shed light on symbiosis as well as a variety of important physiological features. Recent work by Kenny et al, (2019) has already shown that freshwater sponges have extensive gene duplications driving evolutionary novelty and have benefited from symbioses that allow them to live in challenging conditions. Given that E. muelleri has a higher gene content than most animals, nearly twice that of humans (Kenny et al, 2020), it may not be surprising to find a large number of taxonomic specific genes among those that are differentially expressed.…”
Section: Freshwater Sponge:algal Symbiosis As Tractable Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the initial work centered on the ecological importance of photosynthetic sponges in freshwater ecosystems (e.g., Williamson, 1977;Williamson, 1979;Frost & Williamson, 1980) yet freshwater sponge symbioses are poorly represented in the modern algal-based symbiosis literature. The emergence of powerful molecular tools, however, offers renewed opportunities to study sponge-based symbiotic systems, which is aided by the fact that freshwater sponges offer many tractable qualities of a model system (Kenny et al, 2019;Kenny et al, 2020). With modern molecular and cellular tools, however, freshwater sponges are proving to be an exciting tool to study intracellular symbiosis.…”
Section: Introductionmentioning
confidence: 99%